Pengaruh Penguasaan Buku Amtsilati Terhadap Maharah Qira’ah Santri Pondok Pesantren Ngalah Purwosari Pasuruan - Ananda Khoirun Nisa’a (Impressive: Journal of Education, 2023)
Arabic learning in Indonesia, especially the visibility of reading, can be said to be weak. To improve the mastery of Arabic in Dormitory D, there is the Amtsilati Program which aims to help improve the reading skills of students, especially the yellow book. In his learning. The purpose of this study is 1) To find out Amtsilati’s learning activities in Dormitory D 2) To find out the influence of Amtsilati’s book mastery on the Reading Skills of Students of  Dormitory D. The proximity used by researchers in this study is a quality approach. The type of research used by researchers is field study research. Meanwhile, the research instruments used for data collection are interviews, observations and documentation. The results of the research obtained are 1) There are four core activities in the Amtsilati Dormitory D Program, namely Amtsilati Teaching and Learning Activities, Memorization of rules and Nadzam amtsilati, lalaran and sorogan. 2) The influence of mastery of Amtsilati books on the readings skill of students of Ngalah Islamic Boarding School is based on two aspects of factors. First, is the psychic factor, in this case it is the motivation and interest in learning of students, second is the environmental factor.